A 45-Degree Radiographic Method for Measuring the Neck Shaft Angle and Anteversion of the Femur: A Pilot Study. (December 2013) - Teo, Pock Chin; Mohd Kassim, Abdul Yazid; Thevarajan, K
Purpose: To propose a novel method to measure the neck shaft angle and anteversion of the femur using anteroposterior and 45° oblique radiographs. Methods: Three human subjects were used to verify the 45° oblique method. The true neck shaft angle and anteversion of the femur were determined using computed tomography. The true values were compared with the values derived by the 45° oblique method after correcting the distortion using a formula. Results: With the true values based on computed tomography as references, the neck shaft angle and anteversion of the 3 subjects deviated +0.82° to +4.66° and −2.14° to +2.55° in lateral 45° oblique radiographs, respectively, whereas the corresponding values in medial 45° oblique radiographs were +0.98° to +5.93° and −10.09° to +1.58°. The lateral 45° oblique method resulted in smaller range of deviation and were more accurate. Conclusion: This 45° oblique method is useful in surgical planning, especially for femoral derotational osteotomy in children. This new method enables easy calculation of the true neck shaft angle and anteversion, with low radiation exposure.